Simulations of the energy loss of ions at the stopping-power maximum in a laser-induced plasma. (March 2016) - Cayzac, W.; Frank, A.; Ortner, A.; Bagnoud, V.; Basko, M.M.; Bedacht, S.; Blažević, A.; Deppert, O.; Gericke, D.O.; Hallo, L.; Knetsch, A.; Kraus, D.; et al.
Abstract: Simulations have been performed to study the energy loss of carbon ions in a hot, laser-generated plasma in the velocity region of the stopping-power maximum. In this parameter range, discrepancies of up to 30% exist between the various stopping theories and hardly any experimental data are available. The considered plasma, created by irradiating a thin carbon foil with two high-energy laser beams, is fully-ionized with a temperature of nearly 200 eV. To study the interaction at the maximum stopping power, Monte-Carlo calculations of the ion charge state in the plasma are carried out at a projectile energy of 0.5 MeV per nucleon. The predictions of various stopping-power theories are compared and experimental campaigns are planned for a first-time theory benchmarking in this low-velocity range.